Analysis of energy consumption in Finland based on the selected economics indicators. Issue 2 (17th February 2018) - Tabasi, Sanaz; Aslani, Alireza; Naaranoja, Marja; Yousefi, Hossein
ABSTRACT: Energy is one of the main inputs of productions. Therefore, national policies have emphasised on accessibility, availability, and affordability of energy supply. This is very important for energy importers, in particular countries with high dependency on industrial products. Finland is one of such countries that has high-energy consumption due to its cold climate, energy-intensive industries, and low population density. Therefore, security of energy supply to respond domestic consumption is one of the main concerns of the Finnish government. To have a resilience energy supply, it is necessary to understand the energy system in Finland. Energy modelling is a tool that helps policy-makers and researchers to understand the fluctuations and changes in the energy system. This research is to investigate the relationship between energy consumption and selected macro-economic factors in Finland. Therefore, energy consumption in each sector is analysed and the importance of renewable energies is also considered. Finally, a regression model is presented to predict energy consumption.